Calculation of delivered composite dose from Calypso tracking data for prostate cancer: And subsequent evaluation of reasonable treatment interruption tolerance limits. Issue 8 (29th July 2019) - Zhao, Hui; Sarkar, Vikren; Wang, Brian; Rassiah‐Szegedi, Prema; Szegedi, Martin; Jessica Huang, Y.; Huang, Long; Tward, Jonathan; Salter, Bill
Abstract: Purpose: In this study we calculate composite dose delivered to the prostate by using the Calypso tracking ‐data‐ stream acquired during patient treatment in our clinic. We evaluate the composite distributions under multiple simulated Calypso tolerance level schemes and then recommend a tolerance level. Materials and methods: Seven Calypso‐localized prostate cancer patients treated in our clinic were selected for retrospective analysis. Two different IMRT treatment plans, with prostate PTV margins of 5 and 3 mm respectively, were computed for each patient. A delivered composite dose distribution was computed from Calypso tracking data for each plan. Additionally, we explored the dosimetric implications for "worst case" scenarios by assuming that the prostate position was located at one of the eight extreme corners of a 3 or 5 mm "box." To characterize plan quality under each of the studied scenarios, we recorded the maximum, mean, and minimum doses and volumetric coverage for prostate, PTV, bladder, and rectum. Results and discussions: Calculated composite dose distributions were very similar to the original plan for all patients. The difference in maximum, mean, and minimum doses as well as volumetric coverage for the prostate, PTV, bladder, and rectum were all < 4.0% of prescription dose. Even for worst scenario cases, the results show acceptable isodose distribution, with the exception for the combination of a 3 mm PTV margin with a 5 mm position tolerance scheme. Conclusions: Calculated composite dose distributions show that the vast majority of dosimetric metrics agreed well with the planned dose (within 2%). With significant/detrimental deviations from the planned dose only occurring with the combination of a 3 mm PTV margin and 5 mm position tolerance, the 3 mm position tolerance strategy appears reasonable, confirming that further reducing prostate PTV margins to 3 mm is possible when using Calypso with a position tolerance of 3 mm.